The Experiential Value of Online Retailing: a Scale Development and Validation from the Consumeras Perspective (Global Journal of Management and Business Research, 2013)
The main purpose of this research is to develop and validate an instrument to measure consumers’ perceptions regarding the other-oriented value (ethics, status, esteem, and spirituality) of online retailers. This can be considered as an attempt to give a full presentation to the experiential value as conceptualized by Holbrook (1996). This is, to our knowledge, an attempt in the literature to specifically measure the experiential value construct as composed by all of the self-oriented and the other-oriented dimensions. Such effort is particularly relevant since online retailers must understand how consumers perceive and evaluate the ethics (Anderson and Srinivasan, 2003), spirituality, esteem, and status of their websites in the face of severe competition and continually rising consumer expectations. Results offer a support of all of convergent, discriminant, and nomological validities.
Keywords: experiential value; ethics; spirituality; esteem; status; websites; and scale development